The Analysis of Fraudulent Financial Reporting Determinant through Fraud Pentagon Approach (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2017)
The purpose of this study was to analyze the prediction of fraudulent financial reporting with the perspective of pentagon fraud. Pentagon fraud theory is the development of the theories of fraud triangle and fraud diamond. The Pentagon fraud theory adds an element of arrogance in addition to the other four existing elements namely pressure, opportunity, rationalization, and competence or capacity. The population in this study were 157 manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2013-2015. The samples of 46 companies were obtained by using purposive sampling technique, so the analysis unit was 138. Data was analyzed by using descriptive statistical analysis and logistic regression analysis. The test result showed that financial stability, the quality of external auditor, and the number of CEO’s photos in the annual reports of the companies had a positive effect on the prediction of fraudulent financial reporting, while financial targets, liquidity, institutional ownership, monitoring effectiveness, replacement of external auditors, and changes of corporate directors had no significant effect on the prediction of fraudulent financial reporting. The conclusion of this study indicates that unstable financial condition, the quality of corporate audit and the level of CEO’s arrogance can influence the occurrence of fraudulent financial reporting.